Influence of ion implantation in SiC on the channel mobility in lateral n-channel MOSFETs - Strenger, Christian; Uhnevionak, Viktoryia; Burenkov, Alexander; Bauer, Anton; Pichler, Peter; Erlbacher, Tobias; Ryssel, Heiner; Frey, Lothar (Electrochemical Society Inc., 2013)
In this work, the impact of ion implantation into the MOSFET channel region on the channel mobility of electrons is investigated. For this purpose, a systematic investigation of the interface trap density, the interface trapped charge and the field-effect mobility is carried out for MOSFETs with different doping profiles and concentrations in the channel region. It will be demonstrated that implantation into the SiC MOSFET channel does not increase the amount of bulk defects. It leads, however, to a change of the doping concentration, and consequently of the bulk potential (φ). The latter crucially determines the amount of charged interface states, and as a result, represents one determining factor for the channel electron mobility. The experimental data indicates that bulk traps as suggested by Agarwal and Haney (1), are insufficient to explain the low electron mobility in SiC MOSFET inversion channels. © The Electrochemical Society.